Factors Associated with Non-adoption of Technology by Rubber Small holders - Md. Sail, Rahim; Muhamad, Mazanah (Universiti Putra Malaysia Press, 1994)
This study argues that information holds the key to decision-making and change processes, and hence technology adoption among smallholders. To determine the levels of technology adoption among smallholders and factors associated with it, a total of 787 smallholders, key informant smallholders and field officers from selected areas in Peninsular Malaysia were interviewed in groups using the focus group discussion technique. Generally, technology adoption level among rubber smallholders was relatively low. Several factors accounted for this finding, among them were: smallholders attitudes towards new technology, financial constraints, physical limitations (uneconomic holding size and accessibility of holdings), labour shortage, inappropriate technology, land ownership and weakness in extension service and communication support system. These factors were found not to act singly but in various combinations which compounded the problem of information flow decision making and change among smallholders in technology adoption. The constraints faced by the smallholders form negative forces that act against the adoption of recommended practices. Some of these barriers can be overcome or minimized with ule provision and implementation of a systematic flow of information from research to extension and from extension LO smallholders. Information from research to extension should cover 'principle', 'how-to' information, besides relevant circumferential and human resource development information. Information from extension to smallholders should focus mainly on 'how-to' and benefits to be accrued from adopting a technology.